Foundations of Intelligent Systems 17th International Symposium, ISMIS 2008 Toronto, Canada, May 20-23, 2008 Proceedings - An, Aijun; Matwin, Stan; Ras, Zbigniew W.; Slezak, Dominik (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the refereed proceedings of the 17th International Symposium on Methodologies for Intelligent Systems, ISMIS 2008, held in Toronto, Canada, in May 2008. The 68 revised papers presented together with 3 plenary talks were carefully reviewed and selected from over 100 submissions. The papers are organized in topical sections on knowledge discovery and data mining: foundations, advances, mining changes and actional patterns; logic for artificial intelligence, autonomic and evolutionary computation, soft computing, databases and data warehouses, digital library, intelligent information retrieval, text mining, intelligent information systems, knowledge representation and integration, Web service and intelligence, as well as applications.